2019
DOI: 10.1016/j.omtm.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Modified mRNA In Vitro Synthesis Protocol for Heart Gene Therapy

Abstract: Synthetic modified RNA (modRNA) is a novel vector for gene transfer to the heart and other organs. modRNA can mediate strong, transient protein expression with minimal induction of the innate immune response and risk for genome integration. modRNA is already being used in several human clinical trials, and its use in basic and translational science is growing. Due to the complexity of preparing modRNA and the high cost of its reagents, there is a need for an improved, cost-efficient protocol to make modRNA. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Treatment with ribonuclease III (RNase III), an RNase that recognizes and cleaves dsRNA of approximately 22 nucleotides in length, has also been shown to reduce immune-stimulatory response (23). It has also been observed that alteration of IVT components affects the purity of the mRNA, including dsRNA content, leading to greater or less innate immune activation (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with ribonuclease III (RNase III), an RNase that recognizes and cleaves dsRNA of approximately 22 nucleotides in length, has also been shown to reduce immune-stimulatory response (23). It has also been observed that alteration of IVT components affects the purity of the mRNA, including dsRNA content, leading to greater or less innate immune activation (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…1), particularly changing uridine with naturally occurring pseudouridine and 5-methyl-cytosine for cytosine [25], combined with advances in in vitro transcription technologies led to less recognition by TLRs and nucleases. Additionally, the stability and in vivo translation efficiency of modRNA have [26,27] and replacing 5′UTR with one from the fatty acid metabolism gene carboxylesterase 1D (Ces1d) [28].…”
Section: Gene Packaging and Deliverymentioning
confidence: 99%
“…They also optimized the nucleotide concentration to 31.6 mM per reaction, resulting in a 290% higher modRNA yield. This nucleotide optimization led to increased percentage of the capped modRNA, thus reducing its immunogenicity in both human cell lines and primary cardiac cells [27].…”
Section: Modrna Delivery and Translation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in in vitro transcription (IVT) technology from either plasmid-based DNA templates or DNA PCR amplified from plasmids, as well as in delivery vehicles including polymeric-and lipid-based nanoparticles, interest has increased in the use of RNA molecules, including mRNA molecules as therapeutics for human disease [3][4][5][6][7][8]. Examples include loss-of-function mutations such as adenosine deaminase deficiency, ornithine transcarbamylase deficiency, phenylketonuria, hemophilia B and cystic fibrosis.…”
mentioning
confidence: 99%